THE DEVELOPMENT OF INTEREST TOURISM IN MINAHASA DISTRICT - Pongsammin, Yosuadi S; Wuisang, Cinthya E. V.; Rengkung, Michael M (SPASIAL, 2021)
The potential for special interest tourism in Minahasa Regency is contained in the 2011-2031 RTRW as a supporter of the local economy. However, there is still a lack of effort from the local government that has not been maximized in promoting the wmk resulting in the potential for special interest tourism that is not developed optimally. With quantitative descriptive research method that is explorative, this research uses Touliang Oki Village, Leilem Village, Pulutan Village, and Kolongan Atas II Village as case studies. The data collection methods used include field surveys and secondary data to see the potential characteristics of supporting the development of WMC objects, as well as primary data conducted on business actors and craftsmen in the form of questionnaires that will be processed using scoring, followed by weightings that have been ranked based on stakeholder opinions. (government), until it is processed using swot to get the final result in the form of a development concept. The results include that the potential supporting characteristics seen from the 8 aspects of tourism development in each case study area generally have the same drivers and obstacles, then the results of the questionnaire obtained a SWOT factor for the turn-around strategy (WO) which was later revealed to be a development concept. This research also produces the concept of spatial and non-spatial development. This research is also expected to be able to offer a 'tourism development concept', especially special interest tourism in supporting community empowerment and elevating the superior potential. Keywords: craftsmen, potential development characteristics, RTRW Minahasa Regency, special interest tourism, the concept of tourism development.